The ketogenic diet could improve the efficacy of curcumin and Oldenlandia diffusa extract in the treatment of gastric cancer by increasing miR340 expression and apoptosis mediated by autophagy, oxidative stress, and angiogenesis. Issue 12 (11th October 2022) - Xiao, Qiuju; Deng, Bo; Akbari, Abolfazl; Liu, Qisheng; Zhu, Bisheng
Abstract: The pathogenesis of gastric cancer is a multistage process that involves glucose metabolism, inflammation, oxidative damage, angiogenesis, autophagy, and apoptosis. Moreover, microRNA‐340 (miR340) also plays a vital role in tumorigenesis and the biology of gastric cancer as an epigenetic factor. It seems that the use of ketogenic diets (KDs) and plant extracts that have antitumor, anti‐inflammatory, and antioxidant properties can be good treatment options to cure gastric cancer. The aim of this study was to investigate the role of miR‐340 on pathways involved in the pathogenesis of gastric cancer and the improving effects of the KD, Oldenlandia diffusa extract (ODE), and curcumin in the animal model of gastric cancer. One hundred and ten male Wistar rats were divided into control and treatment groups. The expression of miR‐340 along with genes involved in inflammation, oxidative damage, angiogenesis, and apoptosis were assessed. The results showed that the KD and different doses of curcumin and ODE in a dose‐dependent behavior could induce apoptosis and the expression of the Akt/mTORC1 pathway and inhibit inflammation, oxidative damage, and angiogenesis in the gastric tissue of rats with cancer. In addition, there was no significant difference between cancer groups receiving ODE and curcumin. These results also showed that consumption of KD could significantly increase the efficacy of ODE and curcumin which may be due to increasing miR‐340 expression. The results of this study suggested well that the KD along with conventional therapies in traditional medicine can be a useful solution for the prevention and treatment of gastric cancer. Practical applications: Gastric cancer is the third leading cause of cancer death, and genetic and epigenetic factors, including miR‐340, are involved in its pathogenesis. However, the use of ketogenic diets (KDs) and plant products such as curcumin and Oldenlandia diffusa extract (ODE) can play an effective role in inhibiting tumorigenesis in some cancers. Our results showed that the KD and different doses of curcumin and ODE could induce apoptosis and the expression of the Akt/mTORC1 pathway and inhibit inflammation, oxidative damage, and angiogenesis in the gastric tissue. Moreover, the KD could significantly increase the efficacy of ODE and curcumin which may be due to an increase in miR‐340 expression. These findings provide novel perceptions about the mechanisms of the KD, curcumin, and ODE to cure gastric cancer. It suggested that the KD as adjunctive therapy along with conventional therapies in traditional medicine could be considered a useful solution to prevent and treat gastric cancer. Abstract : The ketogenic diets (KD) and different doses of curcumin and Oldenlandia diffusa extract (ODE) could induce apoptosis and the Akt/mTORC1 pathway and inhibit inflammation, oxidative damage, and angiogenesis in the gastric tissue. The KD could significantly increase the efficacy of ODE and curcumin which may be due to an increase in miR‐340 expression. It suggested that the KD as adjunctive therapy along with conventional therapies in traditional medicine could be considered a useful solution to prevent and treat gastric cancer.